The Influence of Social Media Influencers, Instagram Paid Advertising, and Content Marketing on the Buying Interest of Ms. Glow Products in National University Students - Tyan Putri Isnaini; Resti Hardin; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the effect of Social Media Influencers, Instagram Paid Advertising, and Content Marketing on Buying Interest in MS Glow products. This study uses quantitative research methods. The data source for this study used primary data through a questionnaire given to 100 respondents from National University students. In sampling, researchers used non-probability sampling techniques with purposive sampling. The data analysis technique used is multiple linear regression analysis and hypothesis testing using t-statistics processed with SPSS 23 software to test the regression coefficient. Based on the partial research results, it is found that Social Media Influencers have a positive and significant effect on Buying Interest in MS Glow products with a tcount value of 5.246> 1.9849 ttable and a significant value of 0.000 <0.050, Instagram Paid Advertising has a positive and significant effect on Buying Interest in MS Glow products with a tcount value of 3.177> 1.9849 ttable and a significant value of 0.002 <0.050 and Content Marketing has a positive and insignificant effect on Buying Interest in MS Glow products with a tcount value of 0.389 <1.9849 ttable and a significant value of 0.698> 0.050.